Sharia Magashid in the Perspective of Corporate Zakat - Muhammad Nasir; Tri indah Fadhilia Rahma (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the role of sharia magashid in the perspective of corporate zakat, including contemporary ijtihad and the expansion of property entities that need to be issued zakat. Corporate zakat is usually analogous to trade donations, this is in accordance with the opinion of the global Zakat Conference, and is based on the opinion of scholars (Ridlo, 2007, regarding performance) Companies should produce zakat, because the company's presence is as a legal institution or what people think. Therefore, between individuals, after that, there are lending transactions, selling, correlating with outside parties, and also undergoing cooperation. all roles and the results of the conclusions are enjoyed in the same way, including the role of Allah SWT in the zakat arrangement (Reza, 2012). The methodology used in this research is a descriptive qualitative model. The research with this model begins with the steps of collecting primary information, making descriptions, systematically compiling all the data/information and presenting the discussion and analysis in the form of narrative descriptions. This research focuses on literature study, in which the research process prioritizes library data. Or in other terms it is called library research. While library research itself is a research activity that prioritizes data mining by reviewing various literatures such as scientific books, national journal articles.